Cell-intrinsic PD-1 promotes proliferation in pancreatic cancer by targeting CYR61/CTGF via the hippo pathway. (28th September 2019) - Pu, Ning; Gao, Shanshan; Yin, Hanlin; Li, Jian-ang; Wu, Wenchuan; Fang, Yuan; Zhang, Lei; Rong, Yefei; Xu, Xuefeng; Wang, Dansong; Kuang, Tiantao; Jin, Dayong; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a refractory disease. Programmed cell death protein-1 (PD-1) monotherapy has shown strong performance in targeting several malignancies. However, the effect and mechanism of intrinsic PD-1 in pancreatic cancer cells is still unknown. In this study, associations between clinicopathological characteristics and stained tissue microarrays of PDAC specimens were analyzed along with profiling and functional analyses. The results showed that cell-intrinsic PD-1 was significantly correlated with overall survival (OS). Independently of adaptive immunity, intrinsic PD-1 promoted tumor growth in PDAC. Concomitantly, the overexpression of intrinsic PD-1 enhanced cancer proliferation and inhibited cell apoptosis in vitro and in vivo . Mechanistically, PD-1 binds to the downstream MOB1, thereby inhibiting its phosphorylation. Moreover, greater synergistic tumor suppression in vitro resulted from combining Hippo inhibitors with anti -PD-1 treatment compared with the suppression achieved by either single agent alone. Additionally, Hippo downstream targets, CYR61 (CCN1) and CTGF (CCN2), were directly affected by PD-1 mediated Hippo signaling activation in concert with survival outcomes. Finally, the formulated nomogram showed superior predictive accuracy for OS in comparison with the TNM stage alone. Therefore, PD-1 immunotherapy in combination with Hippo pathway inhibitors may optimize the anti-tumor efficacy in PDAC patients via targeting cell-intrinsic PD-1. Highlights: In pancreatic cancer tissues, cell-intrinsic PD-1 is significantly associated with unfavorable clinical outcomes. Cell-intrinsic PD-1 promote cancer proliferation and growth through hippo signal pathway by targeting CYR61 and CTGF. The effect of cell-intrinsic PD-1 depends on the PD-L1 and interacts with MOB1. CYR6 and CTGF are dramatically associated with survival and the formulated nomogram showed superior predictive accuracy for survival.